The Effect of Taxes on the Relative Valuation of Dividends and Capital Gains: Evidence From Dual-Class British Investment Trusts. - Ang, James S; Blackwell, David W; Megginson, William L (Journal of Finance, 1991)
The authors provide evidence that taxes affect equity valuation by studying British investment trusts having otherwise identical classes of cash- and stock-dividend-paying shares outstanding. The authors study 1969-82, a period in which there were two dramatic changes in tax policy. They find that stock-dividend shares, which are convertible into cash-dividend shares, sell at premiums when the tax system favors capital gains and at discounts when the tax advantage of capital gains is reduced. After the 1975 elimination of the tax advantage to stock-dividend shares, the authors observe that investors convert virtually all stock-dividend shares into cash-dividend shares.